ANALISIS ALTERNATIF KEBIJAKAN DALAM PENINGKATAN IMPLEMENTASI PENGELOLAAN TAMAN WISATA ALAM PUNTI KAYU SEBAGAI KAWASAN EKOWISATA - Josephine Sofia Ratri Astuti; Serly Nadya; Alya Maharani; Anzaly Yusra Ramadhani; Galuh Efnol Adzan (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
The management of the Punti Kayu Nature Tourism Park (TWA) in Palembang City currently faces several constraints like declining visitors, damaged facilities, and weak supervision, indicating sub-optimal implementation of ecotourism policies. This study aims to deeply analyze TWA Punti Kayu's management policy implementation using George C. Edwards III's model and determine the most appropriate policy alternative through Multi-Criteria Decision Analysis (MCDA) based on William N. Dunn's criteria. Utilizing a qualitative descriptive method, field data were collected via in-depth interviews, observations, and document reviews. The analysis mainly focused on the management (PT IPC), the Natural Resources Conservation Agency (BKSDA), and the visitors. Policy alternatives were evaluated using three criteria: effectiveness, efficiency, and equity. Three primary alternatives emerged: maintaining the status quo, gradual revitalization through strengthening existing governance with government support, and full government takeover. Weighted value calculations revealed that gradual revitalization obtained the highest score (4.00), followed by full takeover (3.40), and the status quo (2.30). Therefore, it is recommended that PT IPC continues its management until their permit naturally ends in 2029, focusing strictly on gradual governance and facility improvements. Concurrently, the government through BKSDA should actively oversee, guide, and support environmental conservation. This approach is highly realistic both financially and administratively, ensuring optimal operational sustainability without creating any management vacuum.